A Corpus-Based Comparison of Syntactic Complexity in Spoken and Written Learner Language - Park, Shinjae (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2022)
Despite writing and speaking being related activities, their end-products are entirely different. However, previous studies have not shown consistency in terms of grammar use in these two modes. Accordingly, in the present study, I aim to define the syntactic characteristics in these two modes with large-scale data and organized research designs. This study examined 14 indices of syntactic complexity and specific grammar factors in 224 monologues and 139 writings of Korean EFL undergraduates. The results revealed that learners tended to use more finite complement clauses and relative clauses while writing but used because- fragments independently and ‘and’ sentence-initially more frequently while speaking. When compared with previous studies, the characteristics of syntactic complexity of Korean EFL learners, regardless of age, are defined by the use of coordination in speaking and the use of subordination in writing.